A Rare Case of Adult-Onset Still's Disease Presenting with Hypercoagulability and Ocular Vasculitis - Mustofa, Hadi Nugraha; Abdullah Fikri; Surya Darma (HM Publisher, 2025)
Background: Adult-onset Still's disease (AOSD) is a rare systemic autoinflammatory disorder characterized by fever, arthritis, rash, and hyperferritinemia. While AOSD commonly presents with systemic and articular manifestations, it can rarely involve other organ systems, including the eye and the coagulation system. Case presentation: We present a case of an 18-year-old male with AOSD who developed hypercoagulability and ocular vasculitis. The patient presented with high-grade fever, polyarthritis, and the characteristic salmon-pink rash. Laboratory investigations revealed leukocytosis, elevated inflammatory markers, and a significant elevation of serum ferritin. Imaging studies ruled out other diagnoses. During the course of his illness, the patient developed hematomas and was found to have elevated fibrinogen and D-dimer levels, suggestive of hypercoagulability. He also experienced ocular symptoms and was diagnosed with ocular vasculitis. The patient was treated with systemic corticosteroids, methotrexate, and anticoagulation therapy, which led to the resolution of his symptoms. Conclusion: This case highlights the rare and serious complications of AOSD, including hypercoagulability and ocular vasculitis. Early recognition and prompt treatment are crucial to prevent morbidity and mortality associated with these complications.